Numerical study of wall shear stress-based descriptors in the human left coronary artery - S. I. S. Pinto (2016)
The present work is about the application of wall shear stress descriptors - time averaged wallshear stress (TAWSS), oscillating shear index (OSI) and relative residence time (RRT) - to the studyof blood flow in the left coronary artery (LCA). These descriptors aid the prediction of disturbedflow conditions in the vessels and play a significant role in the detection of potential zones ofatherosclerosis development. Hemodynamic descriptors data were obtained, numerically, throughANSYS® software, for the LCA of a patient-specific geometry and for a 3D idealized model. Comparingboth cases, the results are coherent, in terms of location and magnitude. Low TAWSS, high OSI andhigh RRT values are observed in the bifurcation - potential zone of atherosclerosis appearance. Thedissimilarities observed in the TAWSS values, considering blood as a Newtonian or non-Newtonianfluid, releases the importance of the correct blood rheologic caracterization. Moreover, for ahigher Reynolds number, the TAWSS values decrease in the bifurcation and along the LAD branch,increasing the probability of plaques deposition. Furthermore, for a stenotic LCA model, very lowTAWSS and high RRT values in front and behind the stenosis are observed, indicating the probableextension, in the flow direction, of the lesion.